Genetic and phenotypic spectrum in the NONO‐associated syndromic disorder. Issue 2 (25th November 2022) - Roessler, Franziska; Beck, Anita E.; Susie, Ball; Tobias, Bartolomaeus; Begtrup, Amber; Biskup, Saskia; Caluseriu, Oana; Delanty, Norman; Fröhlich, Christine; Greally, Marie T.; Karnstedt, Maike; Klöckner, Chiara; et al.
Abstract: The non‐POU domain‐containing octamer‐binding (NONO) protein is involved in multiple steps of gene regulation such as RNA metabolism and DNA repair. Hemizygous pathogenic variants in the NONO gene were confirmed to cause a rare X‐linked syndromic disorder. Through our in‐house diagnostics and subsequent matchmaking, we identified six unrelated male individuals with pathogenic or likely pathogenic NONO variants. For a detailed comparison, we reviewed all published characterizations of the NONO ‐associated disorder. The combined cohort consists of 16 live‐born males showing developmental delay, corpus callosum anomalies, non‐compaction cardiomyopathy and relative macrocephaly as leading symptoms. Seven prenatal literature cases were characterized by cardiac malformations. In this study, we extend the phenotypic spectrum through two more cases with epilepsy as well as two more cases with hematologic anomalies. By RNA expression analysis and structural modeling of a new in‐frame splice deletion, we reinforce loss‐of‐function as the pathomechanism for the NONO ‐associated syndromic disorder.